(untitled) (Ciudades, 2018)
This presentation is laid out as a general consideration on the value of industrial heritage on those regions with deteriorating industrial heritage that seek to surpass the economic, demographic and social crisis, derived from the deindustrialization processes and massive destruction of jobs, by acting in ways that place value on heritage resources ignored until now into the regional and local development strategies. Some examples from European regions and, in particular, the case of Asturias (Spain) serve as empirical references.